2020
DOI: 10.26434/chemrxiv.12152970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Predictive Model of the Temperature-Dependent Inactivation of Coronaviruses

Abstract: The COVID-19 pandemic has stressed healthcare systems and supply lines, forcing medical doctors to risk infection by decontaminating and reusing single-use medical personal protective equipment. The uncertain future of the pandemic is compounded by limited data on the ability of the responsible virus, SARS-CoV-2, to survive across various climates, preventing epidemiologists from accurately modeling its spread. However, a detailed thermodynamic analysis of experimental data on the inactivation of SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
86
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(89 citation statements)
references
References 16 publications
3
86
0
Order By: Relevance
“…Currently, the most commonly used methods to sterilize or inactivate viruses include treatment using chemical agents, UV irradiation exposure, and heat treatment, which have all been intensively assessed and reported (5)(6)(7)(8)(9)(10). Compared with other methods, one major advantage of heat treatment is its relatively shorter treatment time and simplistic method, along with the ability to be incorporated into various human-occupied space (11)(12)(13), which allows for the technique to be readily implemented into a variety of existing applications or systems that could be readily retrofitted to add rapid pathogen inactivation functionality, such as existing heating, ventilation, and air conditioning (HVAC) systems as well as sewer systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the most commonly used methods to sterilize or inactivate viruses include treatment using chemical agents, UV irradiation exposure, and heat treatment, which have all been intensively assessed and reported (5)(6)(7)(8)(9)(10). Compared with other methods, one major advantage of heat treatment is its relatively shorter treatment time and simplistic method, along with the ability to be incorporated into various human-occupied space (11)(12)(13), which allows for the technique to be readily implemented into a variety of existing applications or systems that could be readily retrofitted to add rapid pathogen inactivation functionality, such as existing heating, ventilation, and air conditioning (HVAC) systems as well as sewer systems.…”
Section: Introductionmentioning
confidence: 99%
“…Heat inactivation is a relatively easy, safe, and efficient method to disinfect coronavirus (CoV), as CoV is an enveloped virus that is surrounded by a lipid bilayer with viral spike proteins projecting from the lipid envelope, where both the envelope and the spike protein are susceptible to heat (14). Previous studies have shown that at a temperature of 56 ℃ and higher, with heat application time typically longer than 1 min, is needed to efficiently inactivate CoVs such as SARS-CoV and MERS-CoV (> 6 Log 10 reduction) (5,6,13). More specifically, at relatively low treatment temperatures (56 -65 ℃), treatment time of 15 -60 min was required, while at higher treatment temperatures (70 -100 ℃) a much shorter duration of 1 to 15 min was needed (5,6,13,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry heat has the potential of satisfying the above five requirements. Heat is one of the most conventional disinfection technologies, so the thermal inactivation efficacies for various pathogens are available 7 . Also, the dry heat was recognized as a decontamination technology with minimal impact on the respirator 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Yap et al 2020[85] Lab-scale, an analytical model, based on Arrhenius equation and rate law.The inactivation of virus follows the first-order kinetics C = C o e -kT . The temperature-dependent denaturation of viral proteins has been explained through Arrhenius equation: ln(k) = −Ea/RT + ln(A).Further, combining the two equations resulted in determining the time of reduction of pathogen by n…”
mentioning
confidence: 99%